Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/1476-511x-10-36
|View full text |Cite
|
Sign up to set email alerts
|

Citrus flavonoids repress the mRNA for stearoyl-CoA desaturase, a key enzyme in lipid synthesis and obesity control, in rat primary hepatocytes

Abstract: Citrus flavonoids have been shown to decrease plasma lipid levels, improve glucose tolerance, and attenuate obesity. One possible mechanism underlying these physiological effects is reduction of hepatic levels of the mRNA for stearoyl-CoA desaturase-1 (SCD1), since repression of this enzyme reduces hyperlipidemia and adiposity. Here, we show that citrus flavonoids of two structural classes reduce SCD1 mRNA concentrations in a dose-dependent manner in rat primary hepatocytes. This is the first demonstration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 35 publications
(38 reference statements)
0
27
0
Order By: Relevance
“…Our hypothesis is supported by studies showing that hesperidin could inhibit both hepatic HMG-CoA reductase and ACAT activities, while increasing fecal cholesterol and LDL receptor mRNA levels in animals and cells (56 -59). Furthermore, it also suppressed the mRNA expression for stearoyl-CoA desaturase, a key enzyme in lipid synthesis in rat primary hepatocytes (60).…”
Section: Discussionmentioning
confidence: 97%
“…Our hypothesis is supported by studies showing that hesperidin could inhibit both hepatic HMG-CoA reductase and ACAT activities, while increasing fecal cholesterol and LDL receptor mRNA levels in animals and cells (56 -59). Furthermore, it also suppressed the mRNA expression for stearoyl-CoA desaturase, a key enzyme in lipid synthesis in rat primary hepatocytes (60).…”
Section: Discussionmentioning
confidence: 97%
“…It is reported that many flavonoids have lipid-lowering effects [14,15]. Luteolin has been reported to reduce the accumulation of lipids in HepG2 cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase of lipoprotein lipase and lecithin acyltransferase (LCAT) on feeding Ficus bengalensis flavonoids and quercetin to such groups was seen by Daniel et al [32]. Work done by Nichols et al [33] showed that citrus flavonoids regulated the transcription of the lowdensity lipoprotein receptor (LDLR) gene in HepG2 cells leading to their hypo-cholesterolemic effects.…”
Section: Discussionmentioning
confidence: 99%